Linguistics at school : (Cambridge University Press, 2010)
Linguistics is a subject that has remained largely confined to the academy, rather than being integrated into school curricula. This is unfortunate but not surprising, as although some teacher education programs include courses on linguistics, it is not comprehensively integrated into teacher education, so it is largely absent from the curriculum. This volume brings together a team of leaders in the field of linguistics and education, to provide an overview of the current state of research and practice. It demonstrates changes which can be made to teaching, such as revising teacher's preparation, developing and implementing practical applications of linguistics in both primary and secondary classrooms, partnering linguists with classroom teachers, and working to improve state and national education standards. The contributors emphasize the importance of collaboration between professional linguists and educators in order to meet a common goal: to raise awareness of the workings of language